2015
DOI: 10.1073/pnas.1509610112
|View full text |Cite
|
Sign up to set email alerts
|

RodZ links MreB to cell wall synthesis to mediate MreB rotation and robust morphogenesis

Abstract: The rod shape of most bacteria requires the actin homolog, MreB. Whereas MreB was initially thought to statically define rod shape, recent studies found that MreB dynamically rotates around the cell circumference dependent on cell wall synthesis. However, the mechanism by which cytoplasmic MreB is linked to extracytoplasmic cell wall synthesis and the function of this linkage for morphogenesis has remained unclear. Here we demonstrate that the transmembrane protein RodZ mediates MreB rotation by directly or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
166
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(182 citation statements)
references
References 25 publications
10
166
1
Order By: Relevance
“…If YodL does specifically target MreB activity, then these results suggest that MreB likely retains at least some of its width maintenance function. Morgenstein et al recently found that the interaction between RodZ and MreB in E. coli is required for MreB rotation but that MreB rotation was not required for rod shape or cell viability under standard laboratory conditions (26). The findings of that study are consistent with prior findings indicating that RodZ is not absolutely required for maintenance of rod shape (25).…”
Section: Figsupporting
confidence: 87%
See 2 more Smart Citations
“…If YodL does specifically target MreB activity, then these results suggest that MreB likely retains at least some of its width maintenance function. Morgenstein et al recently found that the interaction between RodZ and MreB in E. coli is required for MreB rotation but that MreB rotation was not required for rod shape or cell viability under standard laboratory conditions (26). The findings of that study are consistent with prior findings indicating that RodZ is not absolutely required for maintenance of rod shape (25).…”
Section: Figsupporting
confidence: 87%
“…However, in various mutant backgrounds, rodZ can be deleted without loss of rod shape or viability, indicating that RodZ is not absolutely required for MreB's function in maintaining shape (24)(25)(26). Based on these observations and others, it has been proposed that MreB-RodZ interactions may regulate some aspect of MreB activity (10,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanistic link between cell wall synthesis and processive MreB motion, which was recently shown to depend on RodZ35, remains to be fully elucidated but has important implications for cell growth and shape determination. A motor-like enzymatic cycle similar to eukaryotic actinomyosin systems may not be required; localization of MreB to areas of negative membrane curvature could explain circumferential motion21.…”
Section: Discussionmentioning
confidence: 99%
“…Images were acquired using NIS Elements software (Nikon) on both the upright and inverted microscopes. Images for 3D reconstructions and subcellular localization were taken on an upright monolithic aluminum microscope (custom-made, (Morgenstein et al, 2015)) with a 100×/1.49 N.A. objective (Nikon), iXon DU-897 cooled EMCCD camera (Andor Technology), and a homemade LabView software package (National Instruments).…”
Section: Star Methodsmentioning
confidence: 99%